(untitled) (KULT_online, 2013)
The essay collections edited by Antonius Weixler (Authentisches Erzählen, 2012) and Markku Lehtimäki et al. (Narrative, Interrupted, 2012) constitute an attempt to establish authenticity and interruption (in the sense of narrative world-disruption) as key concepts of postclassical narratological research. Authentisches Erzählen consists of a multifaceted account of authenticity, accounting both for genealogical transformations and discipline-specific permutations of the term. For its part, Narrative, Interrupted focuses on potentially disruptive elements of narrative communication, and the contributors seek to analyse such phenomena as anti-causality and narrative world-disruption that structuralist narratology eschewed, while also challenging basic assumptions of contemporary narrative theory. Since interruption is one of the main catalysts of the effect of authenticity, the two volumes productively complement each other and make for an interesting contrapuntal read.